Self-Exciting Point Processes: Infections and Implementations - Meyer, Sebastian (Statistical Science, 2018)
This is a contribution to the discussion of Reinhart's "Review of Self-Exciting Spatio-Temporal Point Processes and Their Applications" [Statist. Sci. 33 (2018)], which synthesizes developments from various research fields. Here, I discuss some experiences from modeling the spread of infectious diseases. Furthermore, I try to complement the review with regard to the availability of software for the described models, which I think is essential in "paving the way for new uses."
EVALuna2:35665